2013
DOI: 10.1007/s13258-013-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-based identification and phylogeny of genomic and proteomic sequences of mosquito-borne flavivirus

Abstract: Mosquito-borne flaviviruses (MBFVs) are important cause of emerging and re-emerging human diseases nearly worldwide, transmitted by arthropod vectors (mostly aedes and culex mosquitoes), with particular reference to yellow fever virus, Japanese encephalitis virus, dengue fever virus, St. Louis encephalitis virus, Murray Valley encephalitis virus, etc. In over 100 countries, more than 2.5 billion people are at risk of infection, and approximately 20 million infections are reported annually. Through the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…We next conducted neutralization assays against ZIKV, utilizing our CTRL, WNV, and DENV plasma. Consistent with the relative antigenic distance from ZIKV, DENV immune plasma showed~10-fold increased capacity to neutralize ZIKV (IC 50 = 1:4,320) compared to WNV immune plasma (Figure 1B) (46,47).…”
Section: In Vitro Characterization Of Wnv Antibodies Elicited Through Natural Infectionsupporting
confidence: 54%
“…We next conducted neutralization assays against ZIKV, utilizing our CTRL, WNV, and DENV plasma. Consistent with the relative antigenic distance from ZIKV, DENV immune plasma showed~10-fold increased capacity to neutralize ZIKV (IC 50 = 1:4,320) compared to WNV immune plasma (Figure 1B) (46,47).…”
Section: In Vitro Characterization Of Wnv Antibodies Elicited Through Natural Infectionsupporting
confidence: 54%
“…Combining nuclear DNA and organellar markers has traditionally improved the understanding of invasive processes, and it is becoming clear that including vertically transmitted endosymbiont or parasitic organisms can provide new insight into the origins of invasive species as well as the diseases they carry (Gupta et al. ; Mobegi et al. ).…”
Section: Identifying Source Populationsmentioning
confidence: 99%
“…Having the different sources of genomic information was essential to this study as the recent introduction limited the genetic resolution of the aphid markers used. Combining nuclear DNA and organellar markers has traditionally improved the understanding of invasive processes, and it is becoming clear that including vertically transmitted endosymbiont or parasitic organisms can provide new insight into the origins of invasive species as well as the diseases they carry (Gupta et al 2014;Mobegi et al 2014). The addition of mtDNA provides information on introgression patterns between diverged populations or subspecies because mtDNA genomes track maternal lineages (McCormick et al 2014).…”
Section: Identifying Source Populationsmentioning
confidence: 99%
“…Previously, Moureau et al [18] identified these three viruses in a sister group to DENV, which encompass the Culex spp. associated group and previous related research suggested that the positioning of these viruses was ambiguous [81]. Nevertheless, individual studies focusing on specific viruses have observed this relationship [82].…”
Section: Phylogenetic Insightsmentioning
confidence: 87%